Konstrukcija tekstilij: preje, tkanine, pletiva - Dobnik Dubrovski, Polona (2019)
Textile Structures: Yarns, Woven Fabrics, Knitted Fabrics. The lecture notes provide basic knowledge in the field of the engineering of line and flat textiles (yarns, woven and knitted fabrics) in a concise and transparent form. The introductory chapter entitled Terminology explains the basic professional terms in the development and production of textiles, the classification and the textile applicability fields. Further chapters entitled Yarn Structure, Woven Fabric Structure and Knitted Fabric Structure deal with the structure of a particular type of textiles with an emphasis on geometric characteristics, constructional parameters and the sub-types of textiles with respect to the weave (in the case of woven and knitted fabrics) and manufacturing techniques. To help understand the substance content, schematic images and realistic images of individual types of textiles are added.
Keywords: textiles; yarns; woven fabrics; knitted fabrics; structure; constructional parameters